First‐Principles Calculations and Optical Absorption Spectrum of a Light‐Colored Aluminum‐Substituted ε‐Iron Oxide Magnet. Issue 3 (5th December 2016) - Nasu, Tomomichi; Yoshikiyo, Marie; Tokoro, Hiroko; Namai, Asuka; Ohkoshi, Shin‐ichi
Abstract : In this paper, we report the electronic structure and optical properties of Al‐substituted ε‐Fe2 O3 . First‐principles calculations of the periodic structure of ε‐Al0.5 Fe1.5 O3 reveal that the band gaps ( E g ) are 2.6 (480 nm) and 2.5 eV (500 nm) for the up‐spin and down‐spin transitions, respectively. To investigate the electronic structure, a highly dispersed polymer solution composed of ε‐Al0.66 Fe1.34 O3 nanoparticles was prepared. This solution is light orange in color; the absorption coefficients ( ε ) are small with values of 810 and 260 dm 3  mol –1  cm –1 at 3.1 (400 nm) and 2.6 eV (480 nm), respectively. The reason why Al‐substituted ε‐Fe2 O3 is so light in color can be understood by the disappearance of the energy states in the conduction and valence bands, which originates from the tetrahedral D site. Such a light‐colored magnetic material should be useful for colored magnetic toners for color printing. Abstract : Periodic structure calculations of Al‐substituted ε‐Fe2 O3 reveal that ε‐Al0.5 Fe1.5 O3 has a wide band gap. A highly dispersed polymer solution of the ε‐Al0.66 Fe1.34 O3 nanomagnet is prepared, and it is very light in color relative to other magnetic ferrites. Such a light‐colored magnetic material should be useful for colored magnetic toners for color printing.